2022
DOI: 10.1186/s13046-022-02523-x
|View full text |Cite
|
Sign up to set email alerts
|

B3GALT4 remodels the tumor microenvironment through GD2-mediated lipid raft formation and the c-met/AKT/mTOR/IRF-1 axis in neuroblastoma

Abstract: Background Beta-1,3-galactosyltransferase-4 (B3GALT4) plays a critical regulatory role in tumor biology. However, the role of B3GALT4 in modulating the tumor microenvironment (TME) of neuroblastoma (NB) remains unknown. Methods Public datasets and clinical NB samples were collected to evaluate the expression and clinical significance of GD2 and B3GALT4 in NB patients. CCK-8, colony formation, and transwell assays and experiments in tumor-bearing mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Studies on the TME have demonstrated that the formation of an immunosuppressive TME contributes to the poor prognosis of NB patients and the limited effectiveness of immunotherapy ( 42 , 43 ). In a previous study conducted by our group, we successfully reconstructed normal blood vessels in a mouse model of NB using a multi-target tyrosine kinase inhibitor (TKI) called Anlotinib ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the TME have demonstrated that the formation of an immunosuppressive TME contributes to the poor prognosis of NB patients and the limited effectiveness of immunotherapy ( 42 , 43 ). In a previous study conducted by our group, we successfully reconstructed normal blood vessels in a mouse model of NB using a multi-target tyrosine kinase inhibitor (TKI) called Anlotinib ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…As will be seen in further details later in this work, there is a tissue- and age-dependent restriction of GD2 expression ( Svennerholm et al, 1991 ; Lammie et al, 1993 ; Huang et al, 2022 ). GD2 biosynthesis is mostly regulated by the activity of different glycosyltransferases, with emphasis on ST8SIA1, B4GALNT1 & B3GALT4 ( Sorokin et al, 2020 ; Sha et al, 2022 ), and is controlled epigenetically, transcriptionally, and post-transcriptionally.…”
Section: Regulation Of Gd2 Expressionmentioning
confidence: 99%
“…This suggests additional levels of regulation differentiating normal from aberrant cells. This distinction can be a result of varying transcriptional regulations in the three genes mainly responsible for GD2 expression ( Sorokin et al, 2020 ; Sha et al, 2022 ). This additionally means that GD2 can be a useful stage-specific marker molecule of developing cells.…”
Section: Regulation Of Gd2 Expressionmentioning
confidence: 99%
See 2 more Smart Citations